CFTR Modulators Dampen Aspergillus-Induced Reactive Oxygen Species Production by Cystic Fibrosis Phagocytes - Currie, Alexander J.; Main, Ellen T.; Wilson, Heather M.; Armstrong-James, Darius; Warris, Adilia (Frontiers in Cellular and Infection Microbiology, 2020)
Excessive inflammation by phagocytes during Aspergillus fumigatus infection is thought to promote lung function decline in CF patients. CFTR modulators have been shown to reduce A. fumigatus colonization in vivo, however, their antifungal and anti-inflammatory mechanisms are unclear. Other treatments including azithromycin and acebilustat may dampen Aspergillus-induced inflammation due to their immunomodulatory properties. Therefore, we set out in this study to determine the effects of current CF therapies on ROS production and fungal killing, either direct or indirect by enhancing antifungal immune mechanisms in peripheral blood immune cells from CF patients upon A. fumigatus infection. Isolated peripheral blood mononuclear cells (PBMCs) and polymorphonuclear cells (PMNs) from CF patients and healthy volunteers were challenged with A. fumigatus following pre-treatment with CFTR modulators, azithromycin or acebilustat. Ivacaftor/lumacaftor treated CF and control subject PMNs resulted in a significant reduction (p < 0.05) in Aspergillus-induced ROS. For CF PBMC, Aspergillus-induced ROS was significantly reduced when pre-treated with ivacaftor alone (p < 0.01) or in combination with lumacaftor (p < 0.01), with a comparable significant reduction in control subject PBMC (p < 0.05). Azithromycin and acebilustat had no effect on ROS production by CF or control subject phagocytes. None of the treatments showed an indirect or direct antifungal activity. In summary, CFTR modulators have potential for additional immunomodulatory benefits to prevent or treat Aspergillus-induced inflammation in CF. The comparable effects of CFTR modulators observed in phagocytes from control subjects questions their exact mechanism of action.